Cardiovascular trials review (Le Jacq Communications, 1996)
The purpose of Cardiovascular Trials Review to review those trials which have made a major impact on the practice of clinical cardiology within the last 5 years. We have included only studies that were published in English and concentrated mainly on publications that have appeared since 1990 and have studied either pharmacological or device therapy. The text is divided into major headings of diseases such as myocardial infarction and unstable angina. In general, we gave priority to prospective randomized trial with preference to multicenter studies and those that included 300 patients or more.